System of spectrally pure hydrogen inflow for Uragan-3M torsatron - Glazunov, G.P.; Volkov, E.D.; Baron, D.I. (Вопросы атомной науки и техники, 2000)
The used today system of hydrogen inflow into Uragan-3M torsatron (U-3M) vacuum chamber does not provide the needed purity of hydrogen during plasma experiments. In view of this, the simple construction of a diffusion Pdmembrane module system for spectrally pure hydrogen inflow was suggested and simulation experiments with experimental module were carried out. The tests on the special stand and in the U-3M vacuum vessel have showed such performances of the experimental module at T = 650°C and 1 at. hydrogen pressure: power for heating is ≈200 watt, hydrogen flow through membrane Q ≈ 1 Torr.l/s (specific hydrogen flow through membrane q ≈ 5.10-2 Torr.l/s.cm2). The preliminary results obtained in this work have given the possibility to start the work design and construction of the system for inflow of spectrally pure hydrogen for the U-3M torsatron. Some details of this system are presented.